Сперматогенез у Amphilina japonica (Goto et Ishii, 1936) (Amphilinidea) - Базитов, А.А.; Ляпкало, Э.В.; Юхименко, С.С. (Вестник зоологии, 1979)
The paper deals with spermatogenesis morphology in Amphilina japonica on the histological and histochemical preparations. Anlarge of testides occurs due to large primary spermatogonia in individuals 0.7-0.8 cm. long. Cytophores have no syncytial structure, spermatocytes in the process of meiosis two divisions retain clearly distinct cell boundaries. In the metaphase of the meiosis first division 20 small bivalents (2n=40) are found in the primary spermatocytes. The diagram of spermatogenesis in the mentioned species coincides with that in the strobilized cestodes, i.e. the number of cells in the cytophores, or spermatophores, increases in the sequence 16, 32, 64.